Kemiskinan (Al-Faqr) dalam Perspektif Hadis - Erwin Hafid (Universitas Islam Negeri Alauddin, 2011)
This writing explored about the poverty. In Islamic perspective, the poverty is resulted from; natural disaster, structured system, human and nature exploitation, political and economic system. The poverty is a real picture of social life, both in village and urban society. There is no guarantee that modernism leads to prosperity. It depends on some factors influencing as mentioned above. Commonly hadis speaking about al-faqr refers to those who have nothing either materally or immaterially. Islam comes to give solution among other by ordering its adherents to pay tax (alms) or infaq